Headmaster Leadership in Increasing Effective School (Case Study of Primary School (SDN) 06 Tae Tukong) - Markus Markus; Muhammad Syukri; Usman Radiana (JETL (Journal of Education, Teaching and Learning), 2019)
The roles and responsibilities of principals and teachers in achieving school success in preparing learning programs or programs are very important. The purpose of this study is to find out (1) the preparation of effective school planning at SDN Tae Tukong; (2) Principal leadership in implementing effective schools in SDN 06 Tae Tukong (3) Supervision of school principals on the implementation of teachers in SDN 06 Tae Tukong; (3) Evaluation of teacher performance at SDN 06 Tae Tukong conducted by the principal; and (4) Supporting and inhibiting factors that influence the leadership of school principals in achieving effective schools at SDN 06 Tae Tukong. This study uses a qualitative approach with a type of case study research. Research results obtained include (1) Planning for improving effective schools in SD 06 Tae Tukong is included in the medium-term school work plan and annual plans; (2) Empowerment of existing resources in schools has been carried out properly in accordance with their respective duties and responsibilities; (3) The principal has implemented measures to improve effective schools; (4) Factors supporting school principals in improving effective schools are the ability of principals to manage all school planning, adequate school facilities, and support from parents; (5) Inhibiting factors in improving effective schools are related to the performance of principals, learning facilities, and teachers lack discipline. Based on the research conducted, it can be concluded that improving the quality of school education is related to the performance of the principal.